Perkembangan Doktrin Sistem dan Keamanan Negara Indonesia - Manukallo Danga, Cosmas (JUSTISI, 2023)
Defense is one of the most important elements in a country because good defense will create a sovereign country. Not only that, the security system is also a benchmark for the sovereignty of a country. Therefore, a country must have a good defense system in order to create a sovereign country. In Indonesia, this has been regulated in article 30 of the 1945 Constitution and Law Number 3 of 2002 concerning national defense. Indonesia has undergone several changes related to the doctrine of state defense and security. The method used in this research is library research. The results of the study concluded that Indonesia has undergone several changes in the Doctrine regarding the state defense and security system where at this time Indonesia has adopted a universal defense system which in previous periods Indonesia adhered to a universal people's defense and security system. However, since the enactment of Law Number 3 of 2002 concerning national defense, the doctrine used to date is a universal defense system.